Furthering Recognition of Lift, Slip, And Trip Hazards in Home Healthcare Environments: Opportunities for Virtual Simulation Training. (September 2018) - Lavender, Steven A.; Sommerich, Carolyn M.; Polivka, Barbara; Darragh, Amy; Wills, Celia; Stredney, Don
Home healthcare workers are exposed to numerous safety hazards within client homes. A virtual simulation training system has been developed to train home healthcare workers to recognize and remediate these hazards where possible. This paper investigates how well study participants could identify lift, slip, and trip hazards within the client's home in the virtual simulation training system.